Teacher's Perception of the Profile of Pancasila Students in Elementary School - Mazda Leva Okta Safitri; Apit Fathurohman; Rudi Hermawan (Universitas Negeri Padang, 2023)
The independent curriculum is the curriculum currently used which emphasizes the profile of Pancasila as a long-term goal. This research is qualitative research with a phenomenology type. This study aims to describe how teachers view the profile of Pancasila students in elementary schools. Data collection techniques in this study used observation, questionnaires, and in-depth interviews with 19 elementary school teachers at an elementary school in South Sumatra. The dimensions of faith and piety to God Almighty are carried out by shaping the attitudes of students inside and outside of learning. The dimension of global diversity, learning/activities that recognize various cultures, as well as preserving and respecting diversity for students. Independence dimension, learning/activities created to enable students to manage themselves, be confident and be responsible. The dimensions of mutual cooperation, learning/activities that teach the attitude of cooperation, caring, cooperation, and mutual cooperation. The dimension of critical reasoning, learning/activities that enable students to be able to distinguish fact from diction or opinion, detect existing problems, and not take theories/opinions for granted. The creative dimension is learning/activities that allow students to create works that can bring up new ideas by not stealing other people's work.